Genomic and evolutionary characteristics of G9P[8], the dominant group a rotavirus in China (2016–2018) - Liu, Xiafei; Wang, Mengxuan; Li, Shan; Li, Jingxin; Xiao, Jinbo; Li, Huiying; Zhang, Qing; Kong, Xiangyu; Wang, Hong; Li, Dandi; Duan, Zhaojun (Frontiers in Microbiology, 2022)
G9P[8] became the predominant rotavirus A (RVA) genotype in China in 2012. To evaluate its genetic composition at the whole-genome level, 115 G9P[8] RVA strains isolated from children under 5 years old were sequenced and characterized. All 13 strains in 2016 and 2017 and an additional 54 strains in 2018 were genotyped as G9-P[8]-I1-R1-C1-M1-A1-N1-T1-E1-H1. The other 48 strains in 2018 were all genotyped as G9-P[8]-I1-R1-C1-M1-A1-N1-T1-E2-H1, with the NSP4 gene characterized as a DS-1-like genotype. The time of the most recent common ancestor (tMRCA) and evolution rates of the VP7, VP4, and NSP4 (E1 and E2) genes of these strains were estimated by Bayesian evolutionary dynamics analysis. We estimated the evolution rates (nt substitutions per site per year) as 1.38 × 10−3 [the 95% highest posterior density (HPD) was 1.09–1.72 × 10−3] for VP7, 0.87 × 10−3 (95% HPD: 0.75–1.00 × 10−3) for VP4, 0.56 × 10−3 (95% HPD: 0.41–0.73 × 10−3) for NSP4-E1, and 1.35 × 10−3 (95% HPD: 0.92–1.86 × 10−3) for NSP4-E2. The tMRCA was estimated to be 1935.4 (95% HPD: 1892.4–1961.3) for VP7, 1894.3 (95% HPD: 1850.5–1937.8) for VP4, 1929.4 (95% HPD: 1892.4–1961.3) for NSP4-E1, and 1969.2 (95% HPD: 1942.2–1985.3) for NSP4-E2. The baseline genetic information in this study is expected to improve our understanding of the genomic and evolutionary characteristics of the rotavirus genome. Furthermore, it will provide a basis for the development of next-generation rotavirus vaccines for humans.